Synthesis of 5‐Amino‐3, 3‐dimethyl‐7‐phenyl‐3H‐[1, 2]oxathiolo[4, 3‐b]pyridine‐6‐carbonitrile 1, 1‐Dioxides. (30th January 2014) - Chioua, Mourad; Samadi, Abdelouahid; Postel, Denis; Balzarini, Jan; Marco‐Contelles, José
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>